Corporate social responsibility and circular economy in social economy entities: bibliometric analysis and systematic literature review - Medina Vidal, Fernando; Hernández Gómez, Elena; Briones Peñalver, Antonio Juan (RAN - Revista Academia & Negocios, 2026)
Purpose: To map and synthesise the literature linking Corporate Social Responsibility (CSR) and the Circular Economy (CE) in Social Economy Entities (SEEs) (2000–2025), combining bibliometric mapping and qualitative synthesis to trace thematic evolution and identify SDG-related research gaps. Methodology: Following PRISMA 2020, a mixed-method review integrated bibliometric analysis of 211 Web of Science-indexed journal articles with in-depth synthesis of 30 core papers, using Bibliometrix and Biblioshiny to map publication trends, key contributors, and thematic development. Results: Findings show a significant acceleration in academic output since 2016. Seven key research domains were identified, including sustainability management, circular business models, and ESG indicators, marking a paradigm shift from isolated normative frameworks toward integrated operational strategies where ethical considerations and resource efficiency converge. Implications: SEEs serve as institutional drivers of inclusive circularity through democratic governance and territorial embeddedness. Findings suggest integrating social indicators, such as decent work and participation, into CE frameworks, highlighting SEEs' role in promoting green jobs, local resilience, and community cohesion. Originality: An original integrative framework for inclusive circularity is established, positioning SEEs as the fundamental link between CSR ethical foundations and circular operational practices. It synthesises the social dimension of circularity, providing a conceptual roadmap to overcome academic fragmentation and guide future sustainable governance.